METHOD OF EFFICIENCY CONTROL OF THE PROCESS OF TECHNICAL OPERATION OF MARINE EQUIPMENT - Дорофєєва, З. Я.; Трішин, В. В.; Урум, Н. С. (Science-based technologies, 2019)
Among the important tasks in the direction of improving the operation of the technical state is the upgrading of the system for collecting, processing and analyzing information on the technical condition and reliability of ships. The article argues that the choice of indicators for assessing the effectiveness of the process of technical exploitation is a responsible stage of analysis, the quality of which depends on the results of analysis and the objectivity of choosing rational solutions. In connection with this for the modern period in the literature devoted to the technical and economic analysis of the efficiency of the operation of complex technical systems, there are three main approaches: the evaluation of the effectiveness of one generalized indicator (monocrystalline or scalar); evaluation by a number of indicators (polycrystalline or vector-on); evaluation of the system of indicators with the allocation of a group of common, most important factors. The timely detection of the moments of degradation processes, which determine the terms of transition to the limiting state and are individual for each type of product, is the main objective of controlling the level of reliability of technology at this stage of its operation. In order to assess the efficiency of the technical operation of the vessels, a large nomenclature of indicators has been developed and applied. Therefore, in order to carry out a comprehensive assessment of the impact of the process of rehabilitation of the marine dismantled dismemberment on the technical and economic efficiency of the technical exploitation of marine, it is necessary to use a vector-time efficiency gap that includes a number of partial usage indicators, reliability and cost-effectiveness with the separation of the group of general, the most important indicators. A comparative analysis of various methods and approaches has shown that the task of estimating and forecasting the indicators of technical and economic efficiency of the technical operation of modern ship complexes taking into account various operational factors, the adopted strategy of their technical operation needs to be addressed using the concept of mathematical modeling.